Hubungan Tingkat Kecemasan Ibu Hamil Dengan Kesiapan Menghadapi Persalinan Di Puskesmas Dolatrayat Kabupaten Karo Provinsi Sumatera Utara Tahun 2022 - Pretti Ginting; Eka Purnamasari; Srilina Br Pinem; Heny Rista (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Anxiety in pregnant women is felt since the first trimester, where anxiety is a result of adapting to physical changes in the body, the uterus starting to enlarge, and changes in the breasts as well as psychological changes. This anxiety continues in the next trimester until the third trimester so it is thought to cause less preparation for childbirth later. The aim of the research was to determine the relationship between pregnant women's anxiety levels and readiness for childbirth at the Dolarayat Health Center, Karo Regency, North Sumatra Province. The type of research is analytical with a cross sectional approach. The population is 62 husbands and a sample of 56 people determined based on criteria. Data collection through distributing questionnaires. Data were analyzed univariately and bivariately. The results of the study showed that the anxiety level of third trimester pregnant women was more moderate (73.2%), and the anxiety level was mild (12%), while the anxiety level was severe (14.2%). More prepared for childbirth (76.8%) and less prepared (23.2%). There is a relationship between the level of anxiety of pregnant women and preparation for childbirth (p 0.004 <0.05). It is hoped that health workers can provide education and motivation to husbands, especially pregnant women, about how to deal with anxiety during pregnancy to avoid disorders during pregnancy and childbirth.